Development of STEM-based Worksheets on Global Warming to Improve Students' Scientific Reasoning Ability - Palian, Yolanda Oktavia; Efwinda, Shelly; Damayanti, Puardmi (Universitas Lambung Mangkurat, 2025)
Scientific reasoning is a thinking skill that students need in the 21st century to prepare them for global challenges. The research aims to develop STEM-based worksheets (Science, Technology, Engineering, and Mathematics) on global warming, which is expected to improve students' scientific reasoning skills. This research includes the Research and Development (R&D) method. This research describes the validity of the worksheet conducted by two Physics Education study program experts. The results show that the STEM-based worksheet is very valid, averaging 93.29%. Thus, the STEM-based worksheet on the topic of global warming that has been designed can be used in high school learning to improve students' scientific reasoning skills.